ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMP NEGERI 10 BINJAI DITINJAU DARI HABITS OF MIND - Tika Ramasari; Hidayat Hidayat (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The aim of this research is to describe junior high school students' mathematical problem solving abilities in terms of thinking habits. This type of research is descriptive qualitative. The instruments used in this study were thinking habit questionnaires and problem solving ability tests. Class VIII students of SMP Negeri 10 Binjai who participated in this study were students who had high, medium and low thinking habits. The results of this study indicate that students with high thinking habits can understand problems, can anticipate planning, can solve problems, and can re-examine work. Students with moderate thinking habits can solve problems, are less prepared to anticipate plans to be made, are less prepared to solve problems, and can re-check the results of a plan. Students with low thinking habits have poor ability to solve problems, cannot think of plans to be made, have poor solving skills in solving problems, and cannot rethink the consequences of solutions.